1997
DOI: 10.1038/bjc.1997.59
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor subtype mRNA expression in human colorectal cancer and normal colonic mucosae

Abstract: Summary Somatostatin analogues may be useful novel agents in the systemic treatment of advanced colorectal cancer, as somatostatin inhibits proliferation in a wide variety of cell types. Here, we report the expression profiles of somatostatin receptor mRNAs in 32 pairs of malignant and normal colonic epithelia. Receptor subtype 2 (hSSTR2) mRNA was detected throughout nearly 90% of both malignant and normal tissue by reverse transcription-polymerase chain reaction (RT-PCR) and in situ hybridization. Subtype 5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Kimura et al also reported that crypt cells of mucosa of GI tract were positive for sstr2A [32]. Laws et al [33] and Raggi et al [6] reported the presence of sstr2 and sstr5 and Hope et al [34] also reported sstr1 in colonic mucosa using RT-PCR. In our present study, both colonic and rectal mucosa demonstrated not only sstr2A immunoreactivity but also sstr1, 2B and 5 in the great majority of crypt cells of GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…Kimura et al also reported that crypt cells of mucosa of GI tract were positive for sstr2A [32]. Laws et al [33] and Raggi et al [6] reported the presence of sstr2 and sstr5 and Hope et al [34] also reported sstr1 in colonic mucosa using RT-PCR. In our present study, both colonic and rectal mucosa demonstrated not only sstr2A immunoreactivity but also sstr1, 2B and 5 in the great majority of crypt cells of GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Buscail et al (13) have shown that hsst2 frequency of expression decreased with the tumor stage (3/6, 1/5, or 0/3 in Duke's stages B, C, and D respectively). Using RT-PCR and in situ hybridization, Laws et al (14) have found that hsst2 mRNA was widely distributed in normal mucosa and stroma in 90% of samples. We found that hsst2 mRNA was expressed at a high frequency throughout all tumor stages without any decrease of expression in advanced stage tumors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, cloning of 5 hSSTR has enabled the expression of individual somatostatin receptor expressions to be determined using techniques such as in situ hybridization, RNA-ase protection and reverse transcriptase polymerase chain reactions (RT-PCR) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Studies using these techniques indicate that there is considerable heterogeneity between and within individual tumors with respect to the density of the individual hSSTRs expressed.…”
Section: Expression and Functional Role Of Somatostatin Receptors In mentioning
confidence: 99%